2021
DOI: 10.7196/ajtccm.2021.v27i1.122
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of Acinetobacter baumannii-associated pneumonia and/or bacteraemia at the intensive care unit of Universitas Academic Hospital, Bloemfontein, South Africa

Abstract: Background. Nosocomial infection with multidrug-resistant (MDR) Acinetobacter baumannii is associated with high mortality rates and the optimal treatment regimen is uncertain. Objectives. To compare outcomes, as well as ICU and in-hospital survival rates of patients with A. baumannii pneumonia and/or bacteraemia who were treated with colistin monotherapy v. colistin/tigecycline combination therapy. Methods. This was a retrospective cross-sectional study of patients admitted to the multidisciplinary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Govender, Todd, Nel, et al [21], claim that candida is the primary cause of healthcare-associated BSIs in SA, with an estimated national incidence risk of 84 cases per 100,000 hospital admissions from 2016 to 2017 (95% CI 81-86). Interestingly, Nogbou, Phofa, Nchabeleng, Musyoki, et al [22,23] identified multidrug-resistant (MDR) Acinetobacter baumannii as a leading cause of HAIs in SA with high mortality rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Govender, Todd, Nel, et al [21], claim that candida is the primary cause of healthcare-associated BSIs in SA, with an estimated national incidence risk of 84 cases per 100,000 hospital admissions from 2016 to 2017 (95% CI 81-86). Interestingly, Nogbou, Phofa, Nchabeleng, Musyoki, et al [22,23] identified multidrug-resistant (MDR) Acinetobacter baumannii as a leading cause of HAIs in SA with high mortality rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Maasdorp et al . [1] have shown that the combination of colistin and tigecycline is considerably more effective in treating Acinetobacter baumannii ( A. baumannii ) infection than colistin alone in a retrospective cross-sectional case series. The number of patients enrolled in the study was small (16 in total), but there was considerably better ICU survival in the colistin-tigecycline treatment group (77.8%) than the colistin only group (28.6%), with survival to hospital discharge being 55.6% and 28.6%, respectively.…”
Section: Editorialmentioning
confidence: 99%